Treatment of Endometrial Cancer in Association with Pelvic Organ Prolapse - Asama Vanichtantikul; Ekkasit Tharavichitkul; Imjai Chitapanarux; Orawee Chinthakanan (Case Reports in Obstetrics and Gynecology)
Background. Uterine malignancy coexistent with pelvic organ prolapse (POP) is uncommon and standardized treatment is not established. The objective of this case study was to highlight the management of endometrial cancer in association with pelvic organ prolapse. Case Report. An 87-year-old woman presented with POP Stage IV combined with endometrioid adenocarcinoma of the uterus: clinical Stage IV B. She had multiple medical conditions including stroke, deep vein thrombosis, and pulmonary embolism. She was treated with radiotherapy and pessary was placed. Conclusion. Genital prolapse with abnormal uterine bleeding requires proper evaluation and management. Concurrent adenocarcinoma and POP can be a difficult clinical situation to treat, and optimum management is controversial.